7 - ‘Open the Servers’: The Implications of Electoral Technology for Kenya’s Democratisation Process - Omwoha, Joyce (Africa Development, 2022)
Digital technologies for elections were introduced in Kenya with a vision that they would bring election reforms through increasing administrative efficiency, reducing long-term costs, and by enhancing transparency in the electoral process would enhance citizenry inclusivity. Despite the voting exercise taking place without a hitch, the 2017 General Election results were dismissed by various stakeholders who called on the Independent Electoral and Boundaries Commission (IEBC) to ‘open the servers’, with witnesses, to use the results inside the servers to verify the ballot papers in the ballot boxes. Promises by IEBC that counting, transmission and verification of results would promote citizens’ rights during the electoral process were not met hence the Swahili phrase, ‘Fungua server’ (Open the servers) was coined. The server became the Holy Grail, the gadget of hope for free and fair elections. Chants of ‘Fungua server’ unveiled the dreaded side of Kenya’s democratisation; of flawed elections and violence that followed. ‘Fungua server’ was a call to free and fair elections. The paradox of technology this article seeks to interrogate was how technology has subverted democratic elections in Kenya; arguing that there is need to demystify the server and focus on electoral transparency as a yardstick of democracy.